2014
DOI: 10.1016/j.neuron.2014.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Tau Prion Strains Propagate in Cells and Mice and Define Different Tauopathies

Abstract: Summary Prion-like propagation of tau aggregation may underlie the stereotyped progression of neurodegenerative tauopathies. True prions stably maintain unique conformations (“strains”) in vivo that link structure to patterns of pathology. We now find that tau meets this criterion. Stably expressed tau repeat domain indefinitely propagates distinct amyloid conformations in a clonal fashion in culture. Reintroduction of tau from these lines into naïve cells re-establishes identical clones. We produced two strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

75
1,030
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 859 publications
(1,109 citation statements)
references
References 71 publications
(112 reference statements)
75
1,030
3
1
Order By: Relevance
“…Supporting this hypothesis, laboratory evidence has shown that disease proteins can travel through local and long-range pathways via transynaptic spread (Frost et al, 2009;Palop and Mucke, 2010;Sanders et al, 2014). Although the relationship between the strength of functional connectivity and underlying white matter integrity is still being examined (Honey et al, 2009;Van Den Heuvel et al, 2009;Hermundstad et al, 2013), the results of our rs-fcMRI analysis are broadly consistent with previously reported patterns of white matter degeneration in svPPA (Acosta-Cabronero et al, 2011;Agosta et al, 2012;Iaccarino et al, 2015).…”
Section: Relating Functional Connectivity To White-matter Pathwayssupporting
confidence: 88%
“…Supporting this hypothesis, laboratory evidence has shown that disease proteins can travel through local and long-range pathways via transynaptic spread (Frost et al, 2009;Palop and Mucke, 2010;Sanders et al, 2014). Although the relationship between the strength of functional connectivity and underlying white matter integrity is still being examined (Honey et al, 2009;Van Den Heuvel et al, 2009;Hermundstad et al, 2013), the results of our rs-fcMRI analysis are broadly consistent with previously reported patterns of white matter degeneration in svPPA (Acosta-Cabronero et al, 2011;Agosta et al, 2012;Iaccarino et al, 2015).…”
Section: Relating Functional Connectivity To White-matter Pathwayssupporting
confidence: 88%
“…Our laboratory previously demonstrated that template-based seeding requires homotypic interactions between seed and substrate (20), consistent with the existence of seeding barriers (33). To test the specificity of our assay, we conducted cross-seeding experiments with the tau biosensor line and measured FRET responses.…”
Section: Resultsmentioning
confidence: 76%
“…In vivo studies have described tau protein spreading from local sites to distant regions, presumably via transsynaptic movement (11,12,(17)(18)(19). Finally, our laboratory and another recently demonstrated that tau propagates discrete amyloid conformations through the brains of animals that give rise to unique neuropathologies (18,20).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The concept of different 'strains' of tau aggregates is consolidated by animal studies demonstrating that the intracerebral injection of brain homogenates from humans with pathologically confirmed PSP, CBD and AGD produced distinct lesions in mouse brains similar to those of the respective human tauopathies [13]. Tau aggregates from different tauopathies from human brain tissue exhibited distinct confirmations or 'strains' and the proteopathic seeds can be transmitted into transgenic mouse brains and be re-introduced to naïve cells to replicate the same structural phenotype and manifest distinct pathological phenotypes [15]. These animal studies support the notion that a 'prion-like' templating mechanism is central to the disease progression in tauopathies [16,17].…”
Section: Propagation and Strainsmentioning
confidence: 99%